Effect of Fresh Banana Plant Waste and its Silage on Dry Matter Intake, Nutrient Digestibility and Rumen Parameters in Osmanabadi Kids - Patil, Shivaram N.; Thirumalesh, T.; Ramachandra, B.; Appannavar, M M; Hiremath, Siddhalinga Swamy; Suranagi, M. D. (Indian Journal of Animal Nutrition, 2019)
Banana plant waste silage was fed to one of the three treatment groups (T3) comprised five kids in each and compared with groups fed fresh banana plant waste (T2) Â and sorghum straw (T1) as source of roughage with concentrate mixture. The silage had pH of 5.05 and DM and CP (%) content of fresh banana plat waste (FBPW) and it silage (FBPWS) was 8.60 and 8.84; 29.97 and 5.44 respectively. The DMI in T2 (0.54%) and T3 (0.98%) groups was significantly (P